Economic valuation of recreation benefits of Putrajaya Lake using Travel Cost Method (TCM) - Nek Abd Aziz Nek Ismail. (2015)
Putrajaya Lake provides important economic benefits to the society. However, these benefits are not easily measured due to unavailable market mechanism. The economic value of recreation benefit needs to be estimated to justify annual budget allocations for managing these lake resources for recreation purposes as well as to evaluate its opportunity cost for conservations to other alternative uses. A study was carried out at Putrajaya Lake, to determine the economic value of recreation benefits received by users. The Individual Travel Cost Method (ITCM) was used to estimate the economic value of recreation benefits of Putrajaya Lake. Data were obtained from survey of 150 visitors using a structured questionnaire during September to December 2014. Two recreation-demand models were used: semi-log and Tobit models to estimate consumers’ surplus based on information on the number of visits, monetary expenses, and other socio economic variables. The estimated average consumer surplus per visit were RM159.74 for semi-log model and RM168.47 for Tobit model. The total consumer surplus per year based on 106,208 visitors were RM16,965,272.37 and RM17,892,910.28 for semi-log and Tobit models, respectively. Using a 10% discount rate with an assumption of no further change in future recreation demand, the total net present value of Putrajaya Lake were from RM169 million to RM178 million. Based on the results of the study, conservation of this lake for recreational purpose should be continued because of this economic benefits to the local community and visitors.